INFLUÊNCIA DA SONOLÊNCIA DIURNA EXCESSIVA E QUALIDADE DO SONO NOS NÍVEIS SÉRICOS DE BDNF E NGF EM ADOLESCENTES. - SILVA JUNIOR, João Ferreira (2020)
Background: The brain-derived neurotrophic factor (BDNF) and neural growth factor (NGF) are widely expressed in the brain and play an important role in neuroplasticity, neurogenesis and increased neuronal connections. Previous studies have found that reduced serum levels of these proteins are associated with sleep disorders in humans. Objective: To analyze the influence of excessive daytime sleepiness (EDS) and sleep quality on serum levels of BDNF and NGF in adolescents. Methods: Cross-sectional population-based study conducted with data from a Brazilian birth cohort, with a sample of 513 adolescents between 18 and 19 years old. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and EDS using the Epworth Sleepiness Scale (ESS). Serum levels of neurotrophins were measured using kits with Luminex™ technology. For analysis, we used marginal structural models, estimated in two steps, a predictive and an explanatory model comparing exposed and unexposed. Results: Adolescents with lower sleep quality didn’t differ from those not exposed in BDNF (p value = 0.191) and NGF (p value = 0.524) levels. Adolescents with EDS had -1.12 pg/ml in the NGF (p value = 0.042). Those who had sleep ≤ 6 hours and sleep efficiency ≤ 75% showed an increase in BDNF by 58.89 pg/ml and 75.14 pg/ml respectively. Those with daytime dysfunction showed reduced BDNF by -62.87 pg/ml. Conclusion: The reduction of NGF in adolescents with EDS and the reduction of BDNF in daytime dysfunction, seems to be related to pressure to sleep, reducing high cortical functions to supply an accumulated deficit or because previous disease. The increase in BDNF in conditions of shorter duration and less sleep efficiency seems to be an adaptive mechanism potentiating neurogenesis and maintaining active neuronal connections, thus reducing cognitive decline.